Effect of substituted β-cyclodextrins on the kinetics of the photochromic processes and hydrolysis of trans-merocyanine - Zsombor Miskolczy; Mónika Megyesi; Gábor Turczel; László Biczók (Carbohydrate Polymer Technologies and Applications)
The effect of β-cyclodextrin (βCD) and its 2-hydroxypropyl, sulfate, and sulfobutyl derivatives was studied to reveal how the host-guest binding influenced the reversible photochromic reactions and the hydrolysis of a trans-merocyanine (trans-MC) dye in acidic and neutral aqueous solutions. Absorption, fluorescence, and NMR spectroscopic measurements demonstrated that the protonated trans-merocyanine (trans-MCH+) produced 1:1 inclusion complex with sulfobutylether- or sulfate-substituted βCD, but the association did not occur with βCD and its 2-hydroxypropyl derivative at pH 2.3. Therefore, only the former cavitands accelerated the photoinduced transformation to the spiropyran (SP) isomer. In contrast, SP was encapsulated in each examined host, and the thermal back conversion from SP to trans-MCH+ was slower within the macrocycles than in water. The unprotonated trans-MC was not incorporated in sulfate-substituted βCD, but the weak complexation with the other employed βCD derivatives catalyzed the hydrolysis of the guest dye at pH 7.